Fabry-Perot interferometer observations of sustained strong vertical wind activity in the auroral thermosphere - Meriwether, J. W.; Larsen, M. F.; Navarro, L. A.; Hampton, D. L. (Frontiers in Astronomy and Space Sciences, 2026)
The vertical component of the neutral wind velocity is critical for understanding the thermospheric dynamics at high latitudes. The neutral vertical wind circulation, driven by auroral activity, redistributes heat and momentum within the lower and upper thermosphere between 100 and 500 km. This flow affects the neutral atmospheric composition, thus contributing to the auroral thermospheric density variability, which is important to the monitoring of neutral density in general and to measuring the orbital satellite drag specifically. We used ground-based vertical wind and temperature observations from Eagle and Fort Yukon narrow field Fabry-Perot interferometer observatories in Alaska along with nearby and collocated Scanning Doppler Imagers, spectrographs, and incoherent scatter radar observations to further understand the physics underlying the production of unexpectedly strong sustained vertical wind (SSVW) events. Our observations found one example of vertical wind velocities of 100 ms−1 together with a temperature increase of 450–500 K. Our analysis suggests that while Joule heating within the lower thermosphere played a significant role during these events, the Alfven F-region heating contribution may also be significant and comparable to the energy associated with soft electrons. This view is based on the work that found that significant auroral heating can result from the thermospheric absorption of Alfvén waves populating “broadband” auroral displays. Overlapping with our FPI observations of strong sustained vertical wind (SSVW) events was detected thermospheric wave activity with maximum vertical wind speeds of 20–30 ms−1 and varying periods from 20 to 40 min, which may be part of the Alfven wave heating process taking place. Thus, both Joule and Alfven wave heating sources taken together may account for the routine incidence of SSVW events as seen in many ground-based narrow field FPI measurements reported over the years.